METHODOLOGY OF TEACHING MATHEMATICS - Ogiloy Bozorova (Web of Journals Publishing, 2024)
Everyone who has knowledge can teach it to others. They teach according to their abilities. To choose the right teaching and learning strategies for a mathematics topic, you need to be aware of various approaches and teaching methods. We explain the distinction between teaching approaches, methods, and techniques as follows.
Keywords: Spiral Approach, Inductive Approach, Deductive Approach, Formal Approach, Competency-Based Approach, Synthetic Approach, Intuitive Approach.